Chemically modified graphenes as detectors in lab-on-chip device - Chua, Chun Kiang (2014)
Graphene materials hold immense potentials for electrochemical detectors in lab-on-chip devices. The electronic and electrochemical properties of graphene based materials are significantly affected by the fabrication routes and by the structural features, such as density of defects and amount of oxygen containing groups. Therefore it is paramount to evaluate various graphene-based materials prior to their integration onto the lab-on-chip devices. The performance of various reduced graphenes (so called chemically modified graphene materials), namely, thermally, chemically and electrochemically reduced graphenes as well as graphene-oxide and graphite-oxide as detectors in a microfluidics system was examined and linked to the materials properties of the various graphenes. This work shows that not all graphene materials are beneficial for the detection at lab-on-chip devices. In addition, the findings show that materials exhibiting excellent properties in batch measurements demonstrate poor performance in flow-setup. These findings could provide valuable insights into the future applicability of graphene materials towards practical applications.